2013
DOI: 10.1063/1.4812727
|View full text |Cite
|
Sign up to set email alerts
|

Using the uncertainty principle to design simple interactions for targeted self-assembly

Abstract: We present a method that systematically simplifies isotropic interactions designed for targeted selfassembly. The uncertainty principle is used to show that an optimal simplification is achieved by a combination of heat kernel smoothing and Gaussian screening of the interaction potential in real and reciprocal space. We use this method to analytically design isotropic interactions for self-assembly of complex lattices and of materials with functional properties. The derived interactions are simple enough to na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Finally, the previous uncertainty inequalities can be still improved for various broad relevant classes of central potentials such as e.g., the convex potentials [ 120 , 121 , 122 , 123 ] and the power-law or anharmonic potentials [ 124 , 125 , 126 , 127 , 128 , 129 ]. This improvement, however, has not yet been done up until now.…”
Section: Dispersion Measures and Heisenberg-like Uncertainty For Central Potentialsmentioning
confidence: 99%
“…Finally, the previous uncertainty inequalities can be still improved for various broad relevant classes of central potentials such as e.g., the convex potentials [ 120 , 121 , 122 , 123 ] and the power-law or anharmonic potentials [ 124 , 125 , 126 , 127 , 128 , 129 ]. This improvement, however, has not yet been done up until now.…”
Section: Dispersion Measures and Heisenberg-like Uncertainty For Central Potentialsmentioning
confidence: 99%
“…Such a) Electronic mail: truskett@che.utexas.edu approaches have found various interactions that stabilize two-dimensional square, honeycomb and kagome lattices [15][16][17][18] as well as the three-dimensional diamond crystal structure. 19,20 Furthermore, it was demonstrated that particles with the optimized interactions indeed assembled into the targeted lattice phases at higher temperature using molecular simulations 15,16,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Highly coordinated lattices with, e.g., face-centered cubic or hexagonal symmetries in three dimensions [7] and triangular symmetry in two dimensions [23] are commonly observed in the experimental assembly of monodisperse particles with short-range, isotropic interactions. A broader array of thermodynamically stable 3D structures-including low-coordinated diamond and simple cubic (Sc) lattices of interest for technological applications [24,25]-has also been demonstrated by computer simulations of monodisperse particles with softer, repulsive potentials [26][27][28][29][30], including those that model the interactions between elastic spheres [31] or star polymers [32]. Similar interactions favor open 2D structures as well, including honeycomb and square lattices [33][34][35][36][37][38][39] with, e.g., sterically stabilized magnetic particles in the presence of an external field [40] providing one novel experimental realization.…”
mentioning
confidence: 99%